Empirical solutions for stress intensity factors of a surface crack in a solid cylinder under pure torsion - Ramezani, Mohammadkazem; Purbolaksono, Judha; Andriyana, Andri; Ramesh, Singh; Putra, Ichsan Setya (Elsevier, 2018)
No empirical solution for the stress intensity factors (SIFs) of a surface crack in a solid cylinder under torsion was reported in literature. In this paper, empirical solutions for Modes I, II, and III stress intensity factors of a semi-elliptical surface crack in a solid cylinder under pure torsion are proposed. The dual boundary element method (DBEM) based software was used to generate the SIFs for different crack size, crack aspect ratio, and different inclination angles. Next, the solutions for the SIFs were produced through a systematic curve fitting approach.